Active Site Identification in FeNC Catalysts and Their Assignment to the Oxygen Reduction Reaction Pathway by In Situ 57Fe Mössbauer Spectroscopy. Issue 2 (18th January 2021) - Ni, Lingmei; Gallenkamp, Charlotte; Paul, Stephen; Kübler, Markus; Theis, Pascal; Chabbra, Sonia; Hofmann, Kathrin; Bill, Eckhard; Schnegg, Alexander; Albert, Barbara; Krewald, Vera; Kramm, Ulrike I.
Abstract : FeNC catalysts are the most promising substitutes for Pt‐based catalysts for the oxygen reduction reaction in proton exchange fuel cells. However, it remains unclear which FeN4 moieties contribute to the reaction mechanism and in which way. The origin of this debate could lie in various preparation routes, and therefore the aim of this work is to identify whether the active site species differ in different preparation routes or not. To answer this question, three FeNC catalysts, related to the three main preparation routes, are prepared and thoroughly characterized. Three transitions A–C that are distinguished by a variation in the local environment of the deoxygenated state are defined. By in situ 57 Fe Mössbauer spectroscopy, it can be shown that all three catalysts exhibit a common spectral change assigned to one of the transitions that constitutes the dominant contribution to the direct electroreduction of oxygen. Moreover, the change in selectivity can be attributed to the presence of a variation within additional species. Density functional theory calculations help to explain the observed trends and enable concrete suggestions on the nature of nitrogen coordination in the two FeN4 moieties involved in the oxygen reduction reaction of FeNC catalysts. Abstract : Based on in situ Mössbauer spectroscopy the contributions of two FeN4 moieties to the direct and indirect oxygen reduction reaction pathway are identified. The D3 doublet contributes to the direct reduction of oxygen, while the D2 doublet is capable of reducing hydrogen peroxide. Density functional theory calculations give insights on the local environment of these two FeN4 moieties.